ANALYSIS OF THE EFFECT OF GROSS SPLIT POLICIES, QUALITY, AND PRICE OF DECISIONS ON THE PURCHASE OF DOMESTIC OPERATING GOODS AT PT. PHE ONWJ - Dian Kumalasari, Elisabeth
Beginning in 2017 is a new round of management of the upstream oil and gas industry. Production Sharing Contracts between the Government and the Cooperation Contract Contractors (KKKS) that initially used the Cost Revovery scheme switched to the Gross Split scheme. The Gross Split scheme is expected to be able to make cashflow and contractor economics more attractive, so that it will encourage investment in the oil and gas sub-sector. In managing operating costs, KKKS with the Gross Split scheme will tend to be more careful and efficient in making decisions on purchasing operational goods because all operating costs incurred will be borne by the KKKS. The existence of information related to the quality and price of domestic operating goods that are less competitive is thought to be one of the factors that influence purchasing decisions, especially for KKKS with the Gross Split scheme. The purpose of this study is to determine whether there is an influence from Gross Split Policies, Quality and Price of Domestic Operating Goods on Purchase Decisions in KKKS. This study uses a quantitative approach through a questionnaire distributed to 34 procurement employees as a population. In addition, researchers also conducted a qualitative approach through interviews with interviewees and Government representatives. The study was conducted at PHE ONWJ KKKS. This study uses multiple linear regression analysis and coding which is then processed using the triangulation method. The results of this study indicate that Gross Split policies does not have significant effect on purchasing decisions at PHE ONWJ, whereas quality and price of domestic operating goods have a significant effect on purchasing decisions at PHE ONWJ KKKS. The researcher suggested several recommendations for the Government to develop domestic industries, that is : (i) Revised Regulations related to Gross Split (Calculation of TKDN not only for goods, but also for services, Supervision of TKDN achievements for the Gross Split KKKS, Using the services of an independent surveyor to validate the achievement of TKDN values , Masterlist for the Gross Split KKKS); (ii) Evaluate the list of APDN; (iii) Development Program for Domestic Producers; (iv) Educational Program for KKKS with Cost recovery and Gross Split scheme; (v) Program to Increase Investment in the Oil and Gas Industry with make a forecast list of goods needs in the short term (1 year ahead) and also the long term (next 5 years); (vi) Appreciation of Innovations carried out by Domestic Producers.